Integrated narrative assessment exemplification: a leukaemia case history - Artioli, Giovanna; Foà, Chiara; Cosentino, Chiara; Sollami, Alfonso; Taffurelli, Chiara (Acta Biomedica Atenei Parmensis, 2017)
Background and aim: In the Integrated Narrative Nursing Assessment (INNA), the Evidence-Based Nursing Model is integrated with the Narrative-Based Nursing Model. The INNA makes use of quantitative instruments, arising from the natural sciences as well as of qualitative ones, arising from the human achieving results of standardization and reproducibility, as well as of customization and uniqueness. Accordingly, the purpose of this work is to exemplify the thinking process of and the method adopted by a nurse adopting an integrated narrative assessment in the evaluation of a patient. Method: The patient suffered from acute myeloid leukaemia, treated with chemotherapy. Her nurse worked in a haematology ward in a North Italy Hospital. The nurse had previous experience in conducting the assessment according to INNA. Based on patient’s characteristics, the nurse chose to use the narration (to explore needs from their subjective perception) and the scales (to measure them objectively) among the various assessment instruments provided by the INNA. Results: The resultant integrated outcomes helped the nurse to have a comprehensive overview of the person’s health-care needs and their connections. These outcomes derive from the integration of narrative information with those obtained from the scales, which in this paper have shown consistent results. Conclusion: It is very difficult to reach this complexity by considering qualitative and quantitative assessment strategies as mutually foreclosing, given that both emerged as being very useful in identifying, understanding and measuring the needs of the assisted person. Then they both could be used to design a customized intervention, encouraging new connections between disease, illness, sickness and everyday life.